Participative decision-making, autonomy, and creative performance: Evidence of match-up employee relations between engineers and managers - Kimpah, Jeniboy; Ibrahim, Hazril Izwar; Rothmann, Sebastiaan; Jaaffar, Amar Hisham (Serbian Journal of Management, 2023)
This study aimed to determine the associations between engineers’ perceptions of participative decision-making and autonomy, and their creative performance. The study utilised a paired match-up technique, with engineers and managers as respondents. Managers were responsible for assessing engineers’ creative performance. Due to the study match-up design, questionnaires measuring participative decision-making, autonomy, and creative performance were distributed to the electrical and electronic manufacturing firms. SmartPLS software was used to analyse the hypothesised relationships. The results indicated that engineers’ participative decision-making significantly predicted autonomy dimensions (work schedule, work criterion, and work method). Engineers’ autonomy regarding work schedule, work criterion, and work method had no positive relationship with creative performance. The results showed that engineers’ work schedule, work criterion, and work method negatively mediated the relationships between participative decision-making and creative performance. The findings indicated an insignificant direct effect and negative mediation of engineers’ work schedule, work criterion, and work method on creative performance, pointing to the structured nature of work. This situation leaves engineers with minimal opportunity to determine the work designs, time allocations, and multicriteria of job descriptions. The study recommends potential directions for studying the improvement of engineers’ creative performance in future studies.